SUN-346 Diffusion Weighted Imaging (DWI) Highlights SDHB-Related Tumours: A Radiation Free Alternative for Surveillance Imaging - Tufton, Nicola (J Endocr Soc, 2019)
Background There is general consensus that asymptomatic carriers of SDHB mutations should undergo periodic surveillance imaging. It is established that (68)Ga-DOTATATE PET/CT is superior for localisation of primary head & neck paragangliomas and SDHB-associated metastatic phaeochromocytoma and paragangliomas (PPGLs). For surveillance, MRI has the major advantage of avoiding radiation exposure. Its sensitivity and specificity for detecting PPGL will be dependent on sequences obtained and expertise of the reporting radiologist. For MRI diffusion weighted imaging (DWI) sequences to compete with PET in terms of sensitivity and specificity, they need to be able to identify small PPGLs at all the possible body sites in which they can occur and ideally metastatic deposits. Method Our SDHB surveillance screening scans include DWI sequences. We reviewed 18 patients with 28 SDHB-related tumours. All these scans had already been comprehensively double reported. We presented the scans to a radiologist, expert in reporting PPGL screening scans, without specifying the location of the tumour (if present) and asked them to use DWI sequences to guide a more focused review. If DWI identified an area of interest, this was then compared with the standard MRI sequences. The site and size of the tumour was recorded, as well as the b values and ADC values for the sequences obtained. Results The DWI sequence identified all 28 tumours. Many false positive areas of focus were noted and excluded. The tumours detected by DWI ranged in size from 5-52mm. Primaries were identified on DWI in the abdomen (n=13), adrenal gland (n=1), thorax (n=3), neck (n=2), and bladder (n=2). Additionally one SDHB-related GIST and two SDH-related RCCs were also highlighted by DWI, as were metastatic deposits in the liver and bone. The smallest metastatic deposits visualised were 5mm. In addition we will present examples of MR images that demonstrate the value of DWI sequences. Conclusion We would recommend, for units not already adding DWI sequences to their MRI screening scans, that these sequences are considered so that a wider experience can be reported on the sensitivity and specificity of the size and location of tumours and metastatic deposits that can be identified. If the sensitivity is confirmed in a larger series and for all SDH subunits, this will provide added reassurance about identifying small SDH-related tumours, without the consequences of exposing the patients to radiation based imaging techniques.